2020
DOI: 10.1111/cod.13629
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of aluminium release from Finn chambers under different in vitro test conditions of relevance for patch testing

Abstract: Background: Contact allergy to aluminium (Al) might pose a risk of false-positive readings of patch-test results when testing with Finn chambers. Objectives: To quantify the release of Al from empty Al Finn chambers, covered Finn Aqua chambers, and Al Finn chambers containing different baseline patch-test substances. Methods: Al Finn chambers of different conditions and with different patch-test substances were tested in artificial sweat and their Al release was analyzed by atomic absorption spectroscopy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Aluminum has been found in toothpaste, antiperspirants, tattoos, eardrops, cosmetic skincare products, and some sunscreens, but the bioavailability of different aluminum compounds is not well investigated. 17 Interestingly, Veien et al 18 reported two patients who may have had a systemically aggravated contact dermatitis at previous vaccination sites caused by a small amount of aluminum oxide in toothpaste. It was postulated that aluminum was systemically absorbed by the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum has been found in toothpaste, antiperspirants, tattoos, eardrops, cosmetic skincare products, and some sunscreens, but the bioavailability of different aluminum compounds is not well investigated. 17 Interestingly, Veien et al 18 reported two patients who may have had a systemically aggravated contact dermatitis at previous vaccination sites caused by a small amount of aluminum oxide in toothpaste. It was postulated that aluminum was systemically absorbed by the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…3,14 One case report suggested testing patients with aluminum chloride hexahydrate 10% in petrolatum if a false negative to 2% is suspected. 19 Hedberg et al 17 found that the amount of aluminum released from Finn chambers ® corresponds to a skin dose of 0.03% to 0.5% of aluminum chloride hexahydrate applied in plastic chambers. In one study of 37 children who were patch tested, aluminum allergy was found in 8 patients with 10% aluminum chloride hexahydrate and in only three patients with 2% aluminum chloride hexahydrate.…”
Section: Discussionmentioning
confidence: 99%
“…11 New chemical analyses from Hedberg et al show, however, that various patch test preparations can induce Al release from Finn chambers in vitro due to Al corrosion. 12 In the study, different batches of FC and FCA were investigated with 32 different baseline preparations. These were exposed to artificial sweat containing 5.0 g/L NaCl, 1.0 g/L urea, 1.0 g/L lactic acid, with the pH adjusted to 6.5.…”
mentioning
confidence: 99%
“…These were exposed to artificial sweat containing 5.0 g/L NaCl, 1.0 g/L urea, 1.0 g/L lactic acid, with the pH adjusted to 6.5. 12 It was found that sodium tetrachloropalladate hydrate (Na-Pd) 3% pet. and caine mix II (CM II), 10% pet.…”
mentioning
confidence: 99%
See 1 more Smart Citation